Studi kasus penanganan masalah perundungan (bullying) di sekolah x kota malang - mahsuni, intan sukma (Maliki Interdisciplinary Journal, 2025)
Bullying is a form of violence commonly found in educational settings and can have significant impacts on the psychological, social, and academic aspects of students, particularly during adolescence. This study aims to examine the strategies implemented by school counselors in addressing bullying at School X in Malang City. A qualitative case study approach was employed, using observation, in-depth interviews with the school counselor, and field documentation. The findings reveal that the most frequent type of bullying was verbal bullying, such as body shaming and derogatory remarks. The counselor adopted an educational and humanistic approach through the “Pengakuan Dosa” (Confession) program, which encouraged students to openly express their problems. This strategy reflects the principles of restorative justice and client-centered counseling, emphasizing empathy and the restoration of social relationships. Despite the school’s limited facilities, such as the absence of a permanent counseling room, interventions were carried out effectively through relational approaches and informal support systems. Bullying management proved effective when it involved collaboration among teachers, students, and parents, while also being adapted to the school’s social context. This study underscores the crucial role of school counselors as psychosocial facilitators in fostering a school climate that ensures emotional safety and is free from violence.